Acehnese and English Subject-Predicate Concord: A Contrastive Analysis - Inas Ghina; Rahil Helmi (Journal of English Teaching and Linguistics, 2023)
Contrastive analysis as a synchronic method in language analysis used in this study to show similarities and differences between languages or dialects in order to solve practical problems related to languages, such as language teaching and translation. Every language has its own rules, which is unique as well as common features. A language shares some the same rules to some extent which benefit English learners to better understand the rules of the target language by knowing the similarities between the language and their target language. This research deals with the descriptions and analyses on Subject-Predicate systems of English and Acehnese languages which shows several similarities and differences. The similar structure found in both language is subject and verb in both languages need an agreement depending on the subject of the sentence.  While the differences can be seen in the position of enclitic of both languages. In Acehnese, the clitics position be found within a verb or a noun. While in English, it appears only within a verb. The example sentences of the two languages have been compared with sufficient examples, making it clear where and how they are identical and different.